BUILDING RESTORATIVE JUSTICE ON CRIME OF MURDER DEALING WITH ISLAMIC CRIMINAL LAW PERSPECTIVE - Bahrul Fawaid (Qistie Jurnal Ilmu Hukum, 2019)
This study aims to explain the restorative justice aspect of crime of murder in the perspective of Indonesian Criminal Law and Islamic Criminal Law. The study method used in this study was a normative legal study. Legal study method was conducted based on the mechanism adopted by most types of legal study which emphasized the reference of legislation. The data used were collected from primary data and secondary data as a result of previous studies, which were then analyzed using synthesis analysis. The study results showed that First, based on the perspective of Indonesian criminal law, crime of murder and abuse could only be resolved through the court. The parties involved did not have the opportunity to play a role in communicating/ mediating in order to find the best solution for them, thus abolishing the opportunity for alternatives to punishment other than imprisonment/death penalty. In Indonesian criminal law, crime of murder and persecution are the domain of the state. Therefore, the authority to determine the settlement is in the hands of the government. Secondly, the perspective of Indonesian criminal law, the victims of crime of murder and persecution systematically will be forgotten parties, so there were many interests of victims/heirs which were not accommodated. Even if there was an opportunity to submit the process demand, it was not easy, it had to be represented by the government (Police and Prosecutors), and the decision was in the hand of the judge (court). Meanwhile in Islamic criminal law, victims/heirs of crime of murder occupy a key position in resolving criminal acts. Keywords: Islamic Criminal Law, Restorative Justice, Murder and abuse